Applying Interventions to Prevent or Reduce Excessive Absences in a High School Setting - Williams, Linda L. (Valdosta State University, 2001)
This action research was conducted in a four-year secondary school in southwestern Georgia to determine if the use of technology and stricter enforcement of the local Board of Education's attendance policy helped in preventing or reducing excessive absenteeism. Interventions were employed over the first three months of the 2001-2002 school year among approximately 850 students in grades 9-12. Phone calls were made to parents/guardians and/or individual contacts were made with students who were absent from class for more than three days. At the end of the three months, absentee rates were reduced by 20% from first semester absentee rates in the previous two school years. The number of students in danger of having credit denied due to excessive absences was also reduced by 37%. Teachers responding to a survey indicated that they believe students are aware of the attendance policy and our efforts to reduce absenteeism, and they also made suggestions for improving our appeals policy. Students' responses to a survey corroborated that they and their parents are aware of the attendance policy and its consequences. Based on statistical data and results of the survey, recommendations were made to investigate purchasing software to generate automated phone calls and to be more consistent in denial of credit when students' excessive absences warrant that action.
Keywords: Attendance policy; Absenteeism; Credit; High school attendance; Telephone in education